Husserl’s phenomenological-communicative project - Gilicka, Magdalena (Lingua Posnaniensis, 2017)
This paper aims to present the phenomenological method in the perspective of the philosophy of communication, without depriving the latter of the great importance, in Husserl’s works. The first part of this paper presents the ideas contained in Idee II…, including also the study of communication and agreement for the mutual exchange of experiences. The second part of this paper is the analysis of the arguments about the intersubjectivity, formulated by Husserl in Medytacje kartezjańskie. The last part presents the late period of Husserl’s works, which did not weaken his communicative analyses. This paper shows the peculiar evolution the German thinker’s views, which partially explains the doubts about the fundaments of the phenomenological method.